Digital Shack-Hartmann wavefront sensing - Rinov Herawan. (2008)
Wavefront sensor is designed to measure both intensity distribution and phase distortion of optical fields in real time and high accuracy. It can be widely used not only in measuring, diagnostic, but also in adaptive opticaI systems to compensate for phase distortions. The most well known and widely used Shack-Hartmann wavefront sensor consists of a lenslet array and a CCD camera. The wavefrontsurface under test is divided into a number of beamlets by a two-dimensional sub-apertures of the lenslet array, and each sub-aperture provides a separate focus on the detector of a CCD camera .Then the image spot arraycaptured by CCD can be used to estimate the wavefront local slopes. The centroids of sub-images generated by each lenslet are tested and the sensor output is a set of {x,y}spot positions. Since the SHWS has some advantages for wavefront measuring of a laser beam with a large aperture, and the noise properties of this sensor are well determinedand it is simple to operate sucha sensor, SHWS became the most popularwavefront sensor for adaptive optics. Generally, the wavefrontestimation procedure may be categorized as e